1998
DOI: 10.3171/foc.1998.5.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic vestibular schwannoma: an unusual clinical entity

Abstract: Hemorrhagic vestibular schwannomas are rare entities, with only a few case reports in the literature during the last 25 years. The authors review the literature on vestibular schwannoma hemorrhage and the presenting symptoms of this entity, which include headache, nausea, vomiting, sudden cranial nerve dysfunction, and ataxia. A very unusual case is presented of a 36-year-old man, who unlike most of the patients reported in the literature, had clinically silent vestibular schwannoma hemorrhage. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Lesion diameter is calculated using the equivalent tumor diameter formula[22] [Figure 4]. This data could confirm an increased bleeding tendency in lesion bigger than 3 cm, as described in previous reports[715] (For an accurate analysis of the cases described to date in literature, we report the main clinical and histopahological features of hemorrhagic VN in Table 1). …”
Section: Discussionsupporting
confidence: 71%
“…Lesion diameter is calculated using the equivalent tumor diameter formula[22] [Figure 4]. This data could confirm an increased bleeding tendency in lesion bigger than 3 cm, as described in previous reports[715] (For an accurate analysis of the cases described to date in literature, we report the main clinical and histopahological features of hemorrhagic VN in Table 1). …”
Section: Discussionsupporting
confidence: 71%
“…The VS is an uncommon intracranial tumor and frequently presents with chronic hearing loss, headache, tinnitus, disequilibrium, and facial numbness, whereas acute overt hemorrhage including subarachnoid hemorrhage (SAH) and ITH as its first presentation is quite rare [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, fewer than 50 cases of hemorrhagic VS have been reported in the English literature . In 2014, Niknafs et al performed a review of the literature and identified 39 cases from 18 published articles .…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that microhemorrhage provides the inciting spark; however, persistent bleeding generally requires a secondary factor that promotes greater arteriovenous pressure or impaired coagulation. Prior reports have outlined several potential secondary triggers, including hypertension, pregnancy, excessive straining (e.g., weight lifting), minor head trauma, and antiplatelet or anticoagulant therapy . The issue of head trauma is particularly relevant to the VS population since older age and disequilibrium may increase fall risk .…”
Section: Discussionmentioning
confidence: 99%